Is Vietnam in need of supportive policies for promoting roots and tubers development? Insights from Quang Binh province - Even, B.; Naziri, D.; Le Thi, H.; Palao, Leo K. (International Potato Center, 2019)
Despite their relative importance to the Vietnamese agri-food system, root and tuber crops are under-represented in terms of supportive policies at national level. The case of Quang Binh province shows the existence of potentially more conducive frameworks at provincial level, recognizing cassava as one the three provincial strategic crops and highlighting the roles of root and tuber crops in general in replacing other crops vulnerable to climate change.